2010
DOI: 10.1016/j.vetpar.2010.02.020
|View full text |Cite
|
Sign up to set email alerts
|

PCR diagnosis of visceral leishmaniasis in asymptomatic dogs using conjunctival swab samples

Abstract: The efficacy of conjunctival swab (CS) as a sampling method for visceral leishmaniasis (VL) diagnosis by PCR of asymptomatic dogs was evaluated. The CS was compared to blood samples (B) and skin biopsies (SB), two less invasive samples potentially useful for massive screening of dogs. Thirty asymptomatic dogs, with serological and parasitological positive tests, were used. The samples were analyzed by two PCR methods: kDNA PCR-hybridization and ITS-1 nPCR. The DNA sample volume used was of 1.0 microL and 10.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
48
2
20

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 21 publications
1
48
2
20
Order By: Relevance
“…However, collection of such specimens is invasive, and requires skilled labor or appropriate facilities. In contrast, conjunctival swabs are fast and easy to collect (2) (3) . Thus, we assessed the suitability of conjunctival swabs as a biological sample for PCR-based diagnosis of canine visceral leishmaniasis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, collection of such specimens is invasive, and requires skilled labor or appropriate facilities. In contrast, conjunctival swabs are fast and easy to collect (2) (3) . Thus, we assessed the suitability of conjunctival swabs as a biological sample for PCR-based diagnosis of canine visceral leishmaniasis.…”
mentioning
confidence: 99%
“…For instance, previous studies demonstrated sensitivity as high as 92% (5) , and 91.7% (10) . In addition, 90% sensitivity was achieved by hybridization, and 83.3% by nested PCR (2) . L. infantum DNA was detected in conjunctival swabs from 95% of symptomatic dogs and 77.5% of asymptomatic dogs that also tested positive on other serological and parasitological tests (3) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the possibility of smegma contamination by contaminated semen is despised, which suggests the passage of Leishmania forms from tissue to the preputial/penile surface. The identification of L. infantum by PCR on conjunctival swab samples from infected dogs is related (Leite et al, 2010), which shows the passage of the parasite from tissue to the mucosae surface in the eye. Diniz et al (2005) found high percentage of amastigote forms of L. infantum on explants of the glans penis and preputial sheath of infected dogs (75% and 80-95%, respectively), but its presence on the smegma was not investigated.…”
Section: Discussionmentioning
confidence: 98%
“…A padronização da PCR realizada a partir de amostras de sangue total de dois cães sintomá-ticos, positivos no exame parasitológico e reagentes na sorologia, detectou DNA de L. infantum chagasi até a diluição do DNA de 1:10, demostrando uma ótima capacidade diagnóstica em amostras de sangue total de cães sintomáticos, corroborando com os dados obtidos por outros autores (Lachaud et al 2002, Gomes et al 2007, Quaresma et al 2009, Leite et al 2010.…”
Section: Discussionunclassified